This research aimed to study status of arbuscular mycrorrhizal fungus (AMF) in mangrove and coastal forest post-tsunami disaster, and to study the relationship of soil phosphorus content and number of AMF spores and AMF infection of mangrove and coastal forest post tsunami disaster. Research results show that there were variability in spore numbers in the field studied. The spore numbers in mangrove forest were found as 359, 235, 118 and 160 spores per 50 g of soil in Meulaboh, Banda Aceh, Pid - AAboe B. Saidi; Sri Wilarso Budi R.; Cecep Kusmana (Forum Pasca Sarjana, 2007)
This research aimed to study status of arbuscular mycrorrhizal fungus (AMF) in mangrove and coastal forest post-tsunami disaster, and to study the relationship of soil phosphorus content and number of AMF spores and AMF infection of mangrove and coastal forest post tsunami disaster.  Research results show that there were variability in spore numbers in the field studied.  The spore numbers in mangrove forest were found as 359, 235, 118 and 160 spores per 50 g of soil in Meulaboh, Banda Aceh, Pidie and Nias respectively.  Meanwhile, in coastal forest were 587, 297, 265 and 158 spores per 50 g in Meulaboh, Banda Aceh, Pidie and Nias respectively.  The root of Rhizophora sp.  and Casuarina equisetifolia were colonized by AMF both in mangrove and coastal forest.  Number of spores were negatively correlated to soil phosphorus content, however, there were tendency of positive correlation between root infection and soil phosphorus content.   Key words: coastal forest, mangrove forest, mycorrhiza